Outcomes of Extended Middle Fossa Approach for Petroclival Tumors in the Elderly - Kaul, Vivian F.; Harris, Micah K.; Kato, Masanari; Finger, Guilherme; Gao, Thomas; Hardesty, Douglas A.; Prevedello, Daniel M.; Ren, Yin; Adunka, Oliver F. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective The aims of the study are (1) to evaluate the extended middle fossa approach (eMCF) for resection of tumors in the petroclivus and anterior cerebellopontine angle (CPA) and (2) to compare surgical outcomes between elderly (≥65 years) and nonelderly patients.Design Retrospective cohort.Setting Tertiary referral center.Participants Adults with petroclival, anterior CPA, or posterior fossa lesions who underwent an eMCF approach from 2012 to 2021 were included in the study.Main Outcome Measure Demographics, symptoms, cranial nerve (CN) function, and postoperative outcomes.Results Twenty-nine patients (mean age of 55 years, 59% females) were identified. Eleven (38%) were ≥65 years (65–79 years). The most common pathology was meningioma (n = 13, 45%), followed by vestibular schwannoma (n = 4, 14%) and squamous cell carcinoma (n = 3, 10%). Nineteen tumors (65.5%) were located in the petroclivus, 7 (24%) involved the cavernous sinus, and 10 (34%) were located in the posterior fossa. The mean tumor maximal diameter was 3.4 cm (range: 1.3–7.9 cm). Gross total tumor resection was accomplished in 15 (52%) patients. Most patients (n = 23, 79%) did not develop new CN deficits postoperatively. Of the 13 patients who had complete pre- and postoperative audiometric data, 69% (n = 9) maintained their hearing. Comparing the elderly versus nonelderly patients, there were no significant differences in the development of new CN palsies (p = 0.14), length of stay (p = 0.91), or incidence of postoperative complications (p = 0.30).Conclusions The eMCF approach provides exposure to the petroclival region, anterior CPA cistern, and posterior fossa for a variety of pathologies. It has a favorable safety profile in the elderly (≥65 years) population with low morbidity.
Keywords: extended middle fossa; Kawase; petroclival; vestibular schwannoma; meningioma; elderly